The Utilization of Sentinel-2 Image Data for Bathymetric Mapping with Satellite Derived Bathymetry Approach - Pratama, Nursapnah Indraini; Kun Cahyono, Bambang (Universitas Gadjah Mada, 2024)
Pembaharuan informasi mengenai kedalaman perairan semakin diperlukan untuk berbagai keperluan seperti monitoring, penelitian, manajemen, dan pemetaan area perairan. Adanya perkembangan teknologi pengindraan jauh dan pemodelan Satellite-Derived Bathymetry (SDB) memungkinkan digunakan untuk memperoleh nilai kedalaman perairan. enelitian ini bertujuan untuk memperoleh nilai kedalaman dengan pendekatan Satellite Derived Bathymetry (SDB) dan pemodelan ekstraksi Stumpf (2003) serta melakukan evaluasi terhadap hasil yang diperoleh. Data yang digunakan dalam penelitian ini adalah data navionics dan data pengukuran SBES. Pada penelitian ini nilai korelasi terbaik dihasilkan dari komposit band hijau (B3) dan merah (B4) sebesar 0,642. RMSE terbaik dengan pemodelan Stumpf (2003) diperoleh 2,46 meter dengan rentang kedalaman 0 s.d 5 meter dengan perbandingan kedalaman Navionics Nauticalchart. Hasil evaluasi ketelitian dari pemodelan Stumpf (2003) sudah memenuhi syarat dari SNI 8202 Tahun 2015 tentang Ketelitian Peta Dasar untuk pembuatan LPI dan LLN skala 1 : 25.000 dengan interval kontur 10 meter. The updating of information on water depth is increasingly essential for various purposes such as monitoring, research, management, and mapping of water areas. The advancement in remote sensing technology and Satellite Derived Bathymetry (SDB) modeling allows obtaining water depth values. This research aims to acquire depth values using the Satellite Derived Bathymetry (SDB) approach and Stumpf (2003) extraction modeling, followed by an evaluation of the obtained results. The data utilized in this study consist of Navionics data and SBES measurement data. The best correlation in this research was achieved from the composite of green (B3) and red (B4) bands at 0.642. The best Root Mean Square Error (RMSE) with the Stumpf (2003) modeling was 2.46 meters within the depth range of 0 to 5 meters compared to Navionics Nauticalchart depths. The accuracy evaluation of the Stumpf (2003) modeling met the requirements of SNI 8202 Year 2015 concerning the Accuracy of Basic Maps for the creation of LPI and LLN at a 1:25,000 scale with a 10-meter contour interval.